ESTIMATION OF FRUIT YIELD AND PARASITIC NEMATODES IN IRRIGATED TOMATO FIELD TREATED WITH ORGANIC AMENDMENTS AND MINERAL FERTILIZER - Bello, I.; Sanusi, J.; Ibrahim, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Field experiments were carried out  at the irrigation research station, Kadawain the Sudan Savanna Zone of Nigeria to estimate  tomato  fruit  yield during the 2007/2008, 2008/09 and 2009/2010 dry seasons and  population of  plant parasitic nematodes  during the  2008/09 and 2009/2010 dry seasons in irrigated tomato field treated with organic amendments and mineral fertilizer (NPK). There were thirty six treatments made up of factorial combinations of three  sources of organic manure; urban waste, neem based and poultry manure each at three  levels (50, 100 and 150 kg N ha-1 equivalent) and four  levels of inorganic compound  fertilizer NPK (0, 150, 300 and 450 kg ha-1). The treatments were laid out in a split plot design replicated three times.  The combinations of manure sources and manure rates were assigned to the main plots while inorganic fertilizer rates were assigned to the sub plots.  Results revealed that application of poultry manure at the highest rate of 150 kg N ha-1equivalent combined with 450 kg ha-1NPK resulted in the highest total fruit yield. Plant parasitic nematodes population was higher at mid sampling period than at the initial or harvest periods
Keywords: Organic Amendments, NPK, Parasitic Nematode Population, Tomato